STRATEGI PENGEMBANGAN DESTINASI WISATA TANJUNG BELIT BERBASIS EKOWISATA - Vita Cecilia; Liliana Dewi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The transition from mass tourism to alternative tourism necessitates an effective strategy for destination development. Tanjung Belit Village, situated within the Bukit Rimbang Baling Wildlife Reserve, holds substantial biodiversity and notable tourism potential. This study aims to identify the village’s ecotourism potential and formulate appropriate development strategies. A descriptive qualitative approach was employed, supported by GAP analysis to compare existing and ideal conditions and SWOT analysis for strategy formulation. Data were collected through purposive and snowball sampling. The findings indicate that Tanjung Belit Village possesses significant ecotourism potential; however, a gap persists due to limited community and managerial capacity in implementing ecotourism principles. Capacity-building programs for local communities, managers, and village authorities are recommended to support sustainable ecotourism development.